2022
DOI: 10.58567/ci01020001
|View full text |Cite
|
Sign up to set email alerts
|

The roles of m6A RNA methylation modification in cancer stem cells: new opportunities for cancer suppression

Abstract: As a reversible post-transcriptional modification, N6-methyladeno sine is the most common form of RNA modification in eukaryotic mRNA. Cancer stem cells (CSCs), which are a subpopulation of cells with self-renewal ability and differentiation potential, have been regarded to be one of the roots of tumor occurrence, recurrence, and metastasis. Currently, numerous studies have demonstrated that m6A RNA modification is critically implicated in the regulation of CSCs stemness or the CSC-like traits of cancer cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The expression difference of RNA m 6 A‐regulated genes in HNSCC and adjacent noncancerous tissues was analyzed by the Kruskal–Wallis test. The Spearman rank correlation test was used to draw the coexpression heatmap of ROR β and RNA m 6 A‐regulated genes with the R package ggplot2 23,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression difference of RNA m 6 A‐regulated genes in HNSCC and adjacent noncancerous tissues was analyzed by the Kruskal–Wallis test. The Spearman rank correlation test was used to draw the coexpression heatmap of ROR β and RNA m 6 A‐regulated genes with the R package ggplot2 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…The Spearman rank correlation test was used to draw the coexpression heatmap of ROR β and RNA m 6 A-regulated genes with the R package ggplot2. 23,24…”
Section: Rna Methylation Of N 6 Adenosine (M 6 A) Analysismentioning
confidence: 99%
“…Cancer stem cells (CSCs) have emerged as a key focus in cancer research due to their involvement in tumor initiation, progression, and therapy resistance. 3,4 CSCs possess self-renewal capabilities and exhibit high tumorigenic potential, contributing to tumor recurrence and metastasis. 5 Identifying the molecular mechanisms that regulate CSCs is of paramount importance for developing effective therapeutic strategies against EC.…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, BRD4 has been implicated in the maintenance of CSC populations and the regulation of stemness-associated genes. 4 Given the importance of BRD4 in cancer biology, it is of particular interest to investigate its role in EC and its potential implications for CSC regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Then we hypothesized that NIK might regulate HCC stemness, which was never been reported before and tumor stemness is tightly involved in tumor progression. [14][15][16] In the present study, we aimed to reveal the effects and underlying mechanisms of NIK on HCC stemness. Through the in vitro and in vivo experiments, we revealed that NIK positively regulated the CSC-like traits of HCC cells.…”
mentioning
confidence: 99%